MANAJEMEN LAYANAN BIMBINGAN KONSELING DALAM MENGATASI BULLYING DI SMPN 13 KOTA TASIKMALAYA - Wulan Triyani; Ade Ikbal Pauji; Amarullah Malik (Program Studi Manajemen Pendidikan Islam, 2024)
Bullying is one of the major sins that pollutes education in Indonesia. A form of moral distortion of violent acts that often occur in schools. The existence of guidance and counseling management has a very important function and role in preventing and overcoming all forms of bullying that occur in the school environment. This study aims to describe and analyze the role and function of guidance and counseling management starting from the aspects of planning, implementation, and evaluation in overcoming bullying at SMPN 13 Tasikmalaya City. This study is a type of qualitative descriptive research. Data collection techniques through in-depth interviews, observation and documentation studies. The results of this study indicate that the management of guidance and counseling at SMPN 13 Tasikmalaya City has been implemented well, this can be seen from, first the planning aspect begins with the preparation of a guidance and counseling service program that culminates in the results of the assessment using the analysis of the type of Developmental Task Inventory (ITP) and Developmental Task Application (ATP) which are used as a reference for the preparation of guidance and counseling service programs for students, second in the implementation stage, the school determines the type of service provided to students including individual, group and classical services as well as responsive services as a form of special service to overcome bullying cases at school, and third evaluation is through direct supervision from the principal and also the monitoring team which is carried out routinely once a semester, which aims to assess the extent to which the implementation of the guidance and counseling service program at SMPN 13 Tasikmalaya City. The results of the evaluation are feedback for improving effective and efficient guidance and counseling service programs